Vibroacoustic therapy in the treatment of patients with COVID-19 complicated by respiratory failure: a pilot randomized controlled trial - Konkayev, Aidos; Bekniyazova, Assema (Frontiers in Medicine, 2023)
Coronavirus infection is a dangerous airborne disease that can lead to serious lung damage.Data on the effectiveness of low-frequency chest vibrations in the treatment of lung diseases are available; however, not so many of them exist. Vibroacoustic pulmonary therapy is a component of physiotherapy that improves lung perfusion and drainage without requiring active patient participation.This study aimed to increase statistical efficiency through maximizing the relevant information obtained from the clinical data. Calculating the sample size to determine the power of subsequent studies was also necessary.A pilot randomized parallel trial involving 60 patients was conducted. The patients were divided into two equal groups, where they received sessions of vibroacoustic pulmonary therapy using the "VibroLung" device in two modes "ARDS" and "Pneumonia," with identical treatment.The patients were >18 years old with detected COVID-19 by PCR and grade 2 and 3 lung lesions detected by CT. Blood sampling was performed in the morning at the same time before and after the hardware massage to determine PaO 2 , PaCO 2 , and P/F.As a result of the test, the following data were obtained: on the first day in the group using the "ARDS" mode, PaO 2 indicators averaged 65, CI 95% [58.6-73.2] and on average 77.5, CI 95%[69.8-85.2], "before" and "after," respectively, which indicates improved oxygenation after the procedure. However, in the second group with the "Pneumonia" mode after its use, PaCO 2 was higher after the session, on average 48.7, CI 95% [40.8-56.6], whereas before that, the following indicators had, on average 43.6, CI 95% [37.2-50].Thus, the data obtained yielded ambiguous results, which are the basis for further study in future randomized controlled trials. As the treatment of coronavirus infection has no etiological treatment, even small shifts in the therapy of this category of patients can be significant.